Leveraging Information Technology to Localize Sustainable Development Goals in Higher Education: A Comparative Study - Paudel, Sushil (International Research Journal of MMC (IRJMMC), 2025)
The incorporation of Sustainable Development Goals (SDGs) into higher education has become an essential approach to preparing young people to confront complex global issues. This research investigates the pivotal role of Information Technology (IT) in facilitating the localization of SDGs within universities, with an emphasis on empowering youth through innovative educational practices. By examining the case of the University of Hertfordshire in the United Kingdom—an institution noted for integrating Artificial Neural Networks into its environmental education programs—the study showcases how artificial intelligence-based learning methodologies can significantly enhance students’ understanding of sustainability concepts. To provide a broader perspective, the study also draws on successful initiatives from Denmark and Finland, where advanced digital teaching strategies, inclusive access to educational resources, and well-structured curricula aligned with SDG 4 (Quality Education) have been implemented effectively. The results suggest that embedding IT within higher education not only improves student engagement and analytical skills but also cultivates a deeper awareness of environmental and social issues. Based on these findings, the study proposes a comprehensive framework for scaling IT-supported SDG education across college and universities in Nepal, aiming to create a more informed, responsible, and capable generation of global citizens.